Studi Komparasi Stabilitas Pipa Bawah Laut dengan DNVGL-RP-F109 dan Elemen Hingga - Nafisa Nandalianadhira; Mochammad Fathurridho Hermanto (Rekayasa, 2023)
Deployment under the sea without being excavated or buried is the most effective alternative. The subsea pipeline must be ensured to be stable on the seabed, not experiencing movement when exposed to environmental forces. There are two main things that must be analyzed in the design process and stability analysis of subsea pipelines, hydrodynamic and hydrostatic forces. In the subsea pipeline design process, one of the most important steps is determining the wall thickness. One standard that is widely used is DNVGL-ST-F101. The diameter and thickness of the subsea pipeline are important parameters for determining subsea pipeline stability. The relationship between the forces acting to the subsea pipeline and the resistance of the soil (seabed) has been regulated in DNVGL-RP-F109. In addition, stability calculations can also be performed based on subsea pipeline modeling on the seabed using the finite element method. Based on these two methods, the vertical and lateral stability of the subsea pipeline can be determined. If the subsea pipeline is unstable, it is necessary to add concrete coating. Based on the pipe properties and environmental data, the wall thickness of the subsea pipeline is 18.203 mm. To be able to meet vertical and lateral stability for operating and installation conditions, 41 mm thick concrete coating is required. The greatest hydrodynamic force occurs in operating condition of 165.693 N/m based on DNVGL-RP-F109 and 154.150 N/m based on finite element. The difference of those result is only 6.96%.